2017
DOI: 10.1021/acs.cgd.7b00872
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Temperature Dependence of Isotactic Polypropylene α-on-β Cross-Nucleation Kinetics

Abstract: A particular kind of heterogeneous nucleation, i.e., cross-nucleation, is sometimes observed in polymorphic substances, when a new crystal structure nucleates on the surface of a crystal of a different modification. Here we show a unique and apparently incongruous nucleation behaviour in polymorphic isotactic polypropylene (i-PP). The rate of cross-nucleation of the monoclinic -phase on the trigonal -phase crystals increases with increasing temperature. This behaviour is contrary to that of the heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…it can be considered that the concentration of heterogeneous nuclei is constant at a given temperature within a certain time interval, cross-nucleation on Form I spherulites is 'pseudo-homogeneous', with the surface density of Form II nuclei linearly increasing with time. 24,27,28 Moreover, the amount of seed surface available for cross-nucleation is similarly time-dependent, being progressively occupied by Form II morphologies growing on the substrate or impinging from neighboring seeds. Therefore, the application of a simple crystallization model, such as the Avrami, is meaningless.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…it can be considered that the concentration of heterogeneous nuclei is constant at a given temperature within a certain time interval, cross-nucleation on Form I spherulites is 'pseudo-homogeneous', with the surface density of Form II nuclei linearly increasing with time. 24,27,28 Moreover, the amount of seed surface available for cross-nucleation is similarly time-dependent, being progressively occupied by Form II morphologies growing on the substrate or impinging from neighboring seeds. Therefore, the application of a simple crystallization model, such as the Avrami, is meaningless.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Cavallo and Alfonso have shown that many more overlooked examples exist in the polymer crystallization literature. [21][22][23] Moreover, systematic extension of a quantitative approach to cross-nucleation to different macromolecules (isotactic poly(1-butene), polypivalolactone and isotactic polypropylene) [23][24][25][26][27][28] allowed us to understand that the nucleation of one polymorph on another can be regarded as a special case of heterogeneous nucleation, unless the parent phase grows at rates comparable to those of the daughter polymorph. 24,28 All the wealth of information so far obtained on cross-nucleation has been exclusively gathered by optical microscopy analysis of the developing morphology.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that nucleation rate at constant undercooling increased by 60 times with decreasing Δ σ/σ from 0.23 to 0.13, which confirms that Δ σ is extremely sensitive for detecting the nucleating ability of a substrate . For what concerns cross‐nucleation, although the kinetics of the process has already been studied for several systems, a detailed description based on Δ σ calculation was not extensively applied.…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally this can be considered a case of hetero‐polymorphic self‐nucleation, similar to the case of the enhanced form II crystallization kinetics produced by self‐nuclei obtained from the melting of trigonal form I crystals in poly(1‐butene) . The recrystallization of the α‐phase from β‐phase self‐nuclei is favored by the larger growth rate of the former polymorph above 140°C, and possibly by the extensive occurrence the of α‐on‐β cross‐nucleation, which presents an overwhelming rate at these temperatures …”
Section: Resultsmentioning
confidence: 89%